The Combined Use of Imaging Approaches to Assess Drug Release from Multicomponent Solid Dispersions - Punčochová, Kateřina; Ewing, Andrew V; Gajdošová, Michaela; Pekárek, Tomáš; Beránek, Josef; Kazarian, Sergei G; Štěpánek, František (Pharmaceutical research, 2017)
PURPOSE: Imaging methods were used as tools to provide an understanding of phenomena that occur during dissolution experiments, and ultimately to select the best ratio of two polymers in a matrix in terms of enhancement of the dissolution rate and prevention of crystallization during dissolution. METHODS: Magnetic resonance imaging, ATR-FTIR spectroscopic imaging and Raman mapping have been used to study the release mechanism of a poorly water soluble drug, aprepitant, from multicomponent amorphous solid dispersions. Solid dispersions were prepared based on the combination of two selected polymers - Soluplus, as a solubilizer, and PVP, as a dissolution enhancer. Formulations were prepared in a ratio of Soluplus:PVP 1:10, 1:5, 1:3, and 1:1, in order to obtain favorable properties of the polymer carrier. RESULTS: The crystallization of aprepitant during dissolution has occurred to a varying degree in the polymer ratios 1:10, 1:5, and 1:3, but the increasing presence of Soluplus in the formulation delayed the onset of crystallization. The Soluplus:PVP 1:1 solid dispersion proved to be the best matrix studied, combining the abilities of both polymers in a synergistic manner. CONCLUSIONS: Aprepitant dissolution rate has been significantly enhanced. This study highlights the benefits of combining imaging methods in order to understand the release process.
Keywords: Spectroscopy, Fourier Transform Infrared; morfoliny; voda; Polymers; Pyrrolidines; magnetická rezonanční tomografie; Polyvinyls; Morpholines; rozpustnost; Magnetic Resonance Imaging; polyvinyly; Drug Carriers; uvolňování léčiv; polyethylenglykoly; spektroskopie infračervená s Fourierovou transformací; Polyethylene Glycols; nosiče léků; pyrrolidiny; Water; Chemistry, Pharmaceutical; Drug Liberation; krystalizace; farmaceutická chemie; Crystallization; Solubility; polymery